1974
DOI: 10.1021/ac60344a024
|View full text |Cite
|
Sign up to set email alerts
|

Analytical applications of reaction-rate-promoting effects. Tris(1,10-phenanthroline)iron(II)-chromium(VI)indicator reaction

Abstract: Several rate-accelerating effects on the oxidation of ferroin by Cr(VI) in sulfuric acid medium are reported. In all cases, these effects are observed in the earlier portions of the reaction profile and no catalyic cycle appears to be associated with them. Conversion of the rate-modifying species to an inactive form by destruction or, mainly, by complexation with Cr(lll) seems to account for the lack of catalytic cycle. Judicious choice of reaction conditions allows the determination (by initial rate measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These authors described the acceleration phenomenon as "promotion" and not catalysis, since the rate modifying species became inactive either by destruction or by complexation with the generated chromium(III). By judicious choice of reaction conditions and by employing initial reaction rate measurements, they quantified microgram amounts of oxalic and citric acid, vanadium(IV), arsenic(III), chromium(VI), hexacyanoferrate(III), and molybdenum(VI) (101). Dutt and Mottola (99) also observed that the ferroin-chromium(VI) reaction, accelerated by oxalic acid was preceded by an apparent induction period in the presence of uric acid.…”
Section: General Kinetic Papersmentioning
confidence: 99%
“…These authors described the acceleration phenomenon as "promotion" and not catalysis, since the rate modifying species became inactive either by destruction or by complexation with the generated chromium(III). By judicious choice of reaction conditions and by employing initial reaction rate measurements, they quantified microgram amounts of oxalic and citric acid, vanadium(IV), arsenic(III), chromium(VI), hexacyanoferrate(III), and molybdenum(VI) (101). Dutt and Mottola (99) also observed that the ferroin-chromium(VI) reaction, accelerated by oxalic acid was preceded by an apparent induction period in the presence of uric acid.…”
Section: General Kinetic Papersmentioning
confidence: 99%
“…In the case of PA-catalysis, PA is never cooxidised but is lost due to the formation of an inert Cr III -PA complex. Thus PA is not a true catalyst and it is better described as a promoter [2]. The chosen substrate, i.e.…”
Section: Introductionmentioning
confidence: 99%